Soil enzymes : influence of sugar industry effluents on soil enzyme activities /: influence of sugar industry effluents on soil enzyme activities. ([2017]) - Maddela, Naga Raju; Golla, Narasimha; Vengatampalli, Rangaswamy
No abstract available